Intrapreneurial intensity of a community higher education institution in Santa Catarina, Brazil - Lamim, Roberta Pedrini; Ghedine, Tatiana; Behling, Gustavo; Llopis, Juan (REGEPE Entrepreneurship and Small Business Journal, 2025)
Objective: To analyze the intrapreneurial intensity of a Community Higher Education Institution (HEI). Methodology/Approach: a quantitative research approach conducted in a Community HEI in the state of Santa Catarina, Brazil. A survey was used to collect primary data from 396 administrative staff members at all hierarchical levels, complemented by document analysis. Main Findings: The Intrapreneurial Intensity Index (III) of the HEI was classified as low. When comparing the III among managers (135) and non-managerial employees (261), no significant difference was found between the groups. Theoretical/Methodological Contributions: contributes to the scientific community by validating the applicability of the III questionnaire in the Portuguese language and academic settings, as well as by triangulating qualitative data with document analysis, adding robustness to the study. Relevance/Originality: The uniqueness of the study lies in the use of the instrument for measuring the III, adapted to the HEI. The significance of the research lies in the replicability of the study in an academic environment, supporting the development of programs for promoting the intrapreneurial organizational culture. Social/Management Contributions: The findings of this study can be applied not only in community HEIs but also in HEIs of various sizes and segments, guiding the possible directions of corporate entrepreneurship.